Social responsibility in economic institutions and consumer protection: The Egyptian Experience is A Model (Journal of Economic Additions, 2020)
This study aims to address the issue of social responsibility in economic institutions and consumer protection, where the institution works in an environment where relations with different elements of society are intertwined affecting and affected, where the environmental pressures exerted on them increase to take into account the contribution more to the achievement of some social goals, and among the most important social issues that the institution must protect is the consumer.the study has found that the pressures of the environment facing the institution in the present time stem from The pressure of consumer protection associations, the state, the consumer, the media, and the environmental forces that pressure the economic institution contributes to the mandatory adoption of social responsibility and adherence to the basic principles directed towards serving the community and consumers, which have become an essential source of excellence and support their survival and ensure their continuity.Keywords: Economic institution; consumer protection; social responsibility.Jel Classification Codes: M14, M21.